2016 IEEE International Conference on Cloud Computing and Big Data Analysis (ICCCBDA) 2016
DOI: 10.1109/icccbda.2016.7529569
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cloud services to the economic growth

Abstract: Abstract-Internet of Things (IoT) and cloud computing has become an intermediate cradle between intelligent objects and applications that make use of the resourcefulness and data provided by these objects. On one side, IoT can get benefit from almost unlimited resource to implement cloud computing management and penning of services related to smart objects and data provision. On the other side, the cloud can benefit IoT by expanding the scope of application operation to address real-time objects. Despite this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Studies extending TPB found that several personal orientation factors promote green buying behavior (Nguyen et al. , 2016; Kazmi et al. , 2016; Kazmi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies extending TPB found that several personal orientation factors promote green buying behavior (Nguyen et al. , 2016; Kazmi et al. , 2016; Kazmi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results are consistent with Aziz (2019), Ahmed and Khan (2019) and contrary to Maroof et al (Maroof et al, 2019), Shafique et al (2019) and Biblop (Biplob, 2017). Further, if we are able to find empirical evidences against the efficient market hypothesis, the same data set upon increasing the sample size, time frame and country, may reflect contrasting outcomes (Kazmi, Abid, Iqbal, & Hai, 2016; Kazmi, Wahab, Zaman, & Kou, 2018). Strategies based on the results will not always lead to consistent returns in future.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…As the carrier of the survival and development of urban residents, a smart community is the concentrated embodiment of the city's overall smartness level, and this is a new concept of community management and a new model of social management innovation. It refers to a community that makes full use of the integrated application of the Internet of Things (IoT), cloud computing, mobile internet, and other new generation information technologies to provide a safe, comfortable, and convenient modern and intelligent living environment for its residents, thus creating a new-management form based on information and intelligent social management and service [1]. The main objectives of developing a smart community include providing sustainable and clean energy, offering good personalized medical services, and facilitating efficient data collection and analysis.…”
Section: Introductionmentioning
confidence: 99%